El grotesco como transpoética y su territorialización en el “grotesco criollo” - Dubatti, Jorge Adrián (2025)
Based on the analysis of Mateo (1923) by Armando Discépolo, we reflect on the “grotesco criollo”, a poetics of Argentine theater that begins with this dramatic text, as a territorialization of the transpoetics of the grotesque. We understand transpoetics in terms of Comparative Theater and Comparative Theatrical Poetics, as a long-lasting poetics which remains constant through the centuries and is territorialized in each epoch and each context with specific variations.